2005
DOI: 10.1002/asi.20169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of personality on technology adoption: An empirical model

Abstract: An innovator's personality along with the perceived attributes of an innovation predicts the rate of diffusion. The current study focuses on the personality factors that determine the likelihood of adoption of a technological innovation. To that end, the study distinguishes between global innovativeness and context-specific innovativeness. An information processing model was tested where technological innovativeness was purported to be indirectly influenced by an individual's global innovativeness, through its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Innovativeness was conceptualized by Midgley and Dowling (1978) as "the degree to which an individual is receptive to new ideas and makes innovative decisions" (p. 236). Vishwanath (2005) found that tolerance for novelty and tolerance for complexity significantly impacted innovativeness. It is reasonable to infer that an innovative person will re-examine traditional values before receiving new ideas and be inclined to take action to try and adopt the innovation.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Innovativeness was conceptualized by Midgley and Dowling (1978) as "the degree to which an individual is receptive to new ideas and makes innovative decisions" (p. 236). Vishwanath (2005) found that tolerance for novelty and tolerance for complexity significantly impacted innovativeness. It is reasonable to infer that an innovative person will re-examine traditional values before receiving new ideas and be inclined to take action to try and adopt the innovation.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Ram and Jung (1994) suggest that "usage needs … tend to vary across consumers who adopt the product at different stages of the lifecycle" (p. 58) and empirically link novelty seeking with early adoption timing, or use innovativeness (see also Venkatesh and Vitalari 1986). Vishwanath (2005) explores preferences and adoption timing across a number of technology hardware products and finds that tolerance for novelty is tied to adoption timing, with early adopters being more tolerant of novelty, while Chau and Hui (1998) show a similar relationship in computer operating systems. This harkens back to Rogers' (2003) statement that early adopters need to handle ambiguity well, as novelty has been defined a key aspect of ambiguity (Budner 1962).…”
Section: Effects Of Early and Late Platform Adopters On Complementsmentioning
confidence: 99%
“…Personality has drawn interest as a predictor perhaps because it has been shown to predict a number of different types of behavior that relate directly or indirectly to Internet usage. Examples include consumer behavior (Kassarjian, 1971), job performance (Barrick & Mount, 1991), academic achievement (Komarraju, Karau, Schmeck, & Avdic, 2011), team performance (Kichuk & Wiesner, 1997), media preferences (Kraaykampa and van Eijck (2005), Internet banking (Grabner-Kräuter & Faullant, 2008), technology adoption (Vishwanath, 2005), online reviews (Picazo-Velaa, Choua, Melchera, & Pearson, 2010), religiosity (Saroglou, 2002) and unethical Internet behavior (Karim, Hidayah, & Nor, 2009). …”
Section: Introductionmentioning
confidence: 99%